2020
DOI: 10.5603/cj.a2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional versus three-dimensional transesophageal echocardiography in percutaneous left atrial appendage occlusion

Abstract: Background: Real-time three-dimensional transesophageal echocardiography (RT3D TEE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…This was clinically important because 3D TEE areas were also 27% larger in patients that had residual shunt after ASD closure suggesting that 2D TEE can underestimate the area of complex-shaped ASDs. Streb and colleagues compared real time 2D TEE with real time 3D TEE in 40 patients during place of a LAA occlusion device and found that there was better device size agreement (weighted Kappa 0.62 vs. 0.28, respectively) with 3D TEE vs. 2D TEE [52] . Kronzon et al [53] used real time 3D TEE for evaluation of residual MR after mitral repair and replacement and found that 3D TEE provided more information than 2D echo including accurate evaluation of the origin of residual MR, the type of ring or prosthesis used, and location, size, shape, and area of the dehisced segment in cases of MV replacement.…”
Section: Perioperative 3d Tee For Procedures Guidance and Valvular Assmentioning
confidence: 99%
“…This was clinically important because 3D TEE areas were also 27% larger in patients that had residual shunt after ASD closure suggesting that 2D TEE can underestimate the area of complex-shaped ASDs. Streb and colleagues compared real time 2D TEE with real time 3D TEE in 40 patients during place of a LAA occlusion device and found that there was better device size agreement (weighted Kappa 0.62 vs. 0.28, respectively) with 3D TEE vs. 2D TEE [52] . Kronzon et al [53] used real time 3D TEE for evaluation of residual MR after mitral repair and replacement and found that 3D TEE provided more information than 2D echo including accurate evaluation of the origin of residual MR, the type of ring or prosthesis used, and location, size, shape, and area of the dehisced segment in cases of MV replacement.…”
Section: Perioperative 3d Tee For Procedures Guidance and Valvular Assmentioning
confidence: 99%
“…However, 3D image reconstruction is required to obtain LAA shape images, and LAA morphology changes cannot be shown with the cardiac cycle in real time, making this method time-consuming, laborious, and requiring high human interference. Previously, some researchers considered 2D-TEE as the gold standard for the preoperative measurement of relevant morphological parameters in LAAO, but with the rapid development of three-dimensional ultrasound, an increasing number of studies have shown that the results of RT3D-TEE are more accurate and reliable and correlate better with the implanted occluder, making it more suitable as a key reference for the selection of occluder models for LAAO patients ( Morcos et al, 2018 ; Streb et al, 2019 ). However, in addition to its inability to directly display the overall external contour of the LAA, conventional RT3D-TEE still has several limitations such as cumbersome and time-consuming operation procedures when measuring the anatomical and physiological parameters of the LAA ( Morais et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…3D-ЧпЭхоКГ обеспечивает отличный обзор анатомии ЛП до процедур абляции ФП, и эти процедуры связаны с благоприятным долгосрочным результатом [45]. 3D-ЧпЭхоКГ позволяет лучше оценить морфологию УЛП и более точно определить площадь отверстия УЛП, чем 2D-ЧпЭхоКГ, что важно при подборе размера окклюзирующего устройства, а результаты измерения связаны с меньшей изменчивостью, зависящей от специалиста, проводящего исследование, и более высокой надёжностью исследования [46][47][48][49][50][51][52][53][54].…”
unclassified